If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3 = z Combine like terms: 4 + 3 = 7 7 = z Solving 7 = z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 7 + -1z = z + -1z Combine like terms: z + -1z = 0 7 + -1z = 0 Add '-7' to each side of the equation. 7 + -7 + -1z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1z = 0 + -7 -1z = 0 + -7 Combine like terms: 0 + -7 = -7 -1z = -7 Divide each side by '-1'. z = 7 Simplifying z = 7
| 16m+12p= | | 5x+x-5x=7-2x-4 | | 6-(x+3)=9(3x-6) | | 2t+7t-4=5 | | 4(3g-5)=-2(4b+3g) | | 3y^2-18y=93 | | 10x+.5=48 | | -3y-47=y-(65) | | x^3+5x^2+4x-10=y | | 20p+4= | | 3x(17+15)=108 | | -2x=x-(6-2x) | | 9(z+1)-4z=-21 | | 3k^2-42k-15=0 | | 4x+8-2x=3x-7 | | Y=xsquared+x | | 3k^2-42d-15=0 | | -6y-7=-2 | | X^2-(x^3+3)x=-2 | | 0.8g+0.6=2g | | 4m-5=3m-7 | | R(9-6)= | | 2.4+3.9y=y+77.3 | | 12-(2y-4)=18 | | 7.7+8.1y=y+16.8 | | -4+2g-(8g-9)=17 | | 3x^2-2x+4=5 | | X^2-(x^3)x=-2 | | ab(b)=3ab | | 5b-3b=4-2 | | -5+w=16 | | (3x-4)+5(2x+3)=-9 |